EFEKTIVITAS PENYELESIAN SENGKETA ADAT MELALUI PERADILAN ADAT: STUDI DI DESA LAWE SEMPILANG KECAMATAN LAWE ALAS KABUPATEN ACEH TENGGARA - Purnama, Ebi; Syuib, Muhammad; Umur, Azmil (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
This article examines the authority and effectiveness of customary courts as a form of alternative dispute resolution, using a case study in Lawe Sempilang Village, Southeast Aceh. Customary courts serve indigenous communities in resolving both civil and criminal disputes based on local norms. Although accepted by the community, their decisions lack binding legal force and may be challenged through formal judicial processes. Using an empirical juridical approach, the research analyzes data collected through interviews, observation, and document review. The findings indicate that customary courts are effective when the imposed sanctions—such as fines or compensation—are respected by the offender. However, if non-compliance occurs, the aggrieved party may seek recourse through state legal institutions. This study underscores the importance of formal recognition and legal mechanisms to enforce customary decisions and suggests better integration between customary and state justice systems to enhance access to culturally responsive legal remedies.